EKSISTENSI PRINSIP-PRINSIP SURAT BERHARGA SYARIAH NEGARA SEBAGAI INSTRUMEN PEMBIAYAAN - Hariati, Sri (The Juris, 2025)
This study aims to determine and analyze the basic principles of the operation of State Sharia Securities (SBSN) in Indonesia and to determine the existence of State Sharia Securities (SBSN) as one of the financing instruments. The formulation of the problem to be discussed is how are the basic principles of the operation of State Sharia Securities (SBSN) in Indonesia and how is the existence of State Sharia Securities (SBSN) as one of the financing instruments. The type of normative legal research, the approach method includes a statute approach, a conceptual approach, analyzed by the method of data analysis collected then processed and analyzed qualitatively, namely data analysis and legal interpretation. The research results show that its operations use the principles of ijarah, mudharabah, musyarakah and istisna', with general principles based on the principle of halal, and avoiding prohibited investments, gharar, usury and maysir, which prohibit investment activities and the existence of State Sharia Securities as financing and investment instruments can be seen from the mechanisms and stages of the SBSN or state sukuk instruments, which conclude that the position of State Sharia Securities in the legal system in Indonesia has the same position as conventional securities.